Aislamiento de dos Cepas Nativas del Hongo (Beauveria bassaiana) para el control de la broca del Café (Hypothenemus hampel) con tres tipos de concentraciones de unidades formadoras de colonias en el laboratorio de microbiología de la Universidades Estatal de Bolívar - Yánez Márquez, Luis Alejandro (2017)
The use of beneficial organisms today is being applied in many countries especially in the areas of research on biological controls, why by this project sought to encourage this type of work, in this case an entomopathogenic fungus many used pests such as is the fungus (Beauveria bassiana), which was reproduced in the laboratory of microbiology at State University of Bolivar, to control the coffee berry borer (Hypothenemus hampei) for the purpose of counting a one step for management integrated pest, which is to control initiative with a living organism and the organic time, because in our country have not yet created laws that promote alternatives pleasant environment. In this research the following objectives 1 raised) separating two native strains of Beauveria bassiana in coffee soils present in the Caluma Canton. 2) Determine the activity entomopathogenic species (Beauveria bassiana) on (Hypothenemus hampei). 3) Measure the effect of the fungus on the bit in the laboratory. 4) Know what the ideal of colony forming units of Beauveria bassiana to control the coffee berry borer concentration. The design was completely random (DCA) with a factorial arrangement 2x3x4 with 6 treatments and 4 repetitions: analysis of variance, Tukey 5% effect analysis for the factor was performed to compare the average of treatments, A , correlation analysis and linear regression and analysis of orthogonal polynomials for factor B. the highest average yields were for strain and concentration of treatment; T3: farm Cepa win + 5 * 10 CFU / ml, followed by treatment and concentration; T6: Cepa farm Llaguno + 5 * 10 -10 CFU / ml, which having higher concentration of colony forming units showed better results in all the variables. The use of beneficial organisms today is being applied in many countries especially in the areas of research on biological controls, why by this project sought to encourage this type of work, in this case an entomopathogenic fungus many used pests such as is the fungus (Beauveria bassiana), which was reproduced in the laboratory of microbiology at State University of Bolivar, to control the coffee berry borer (Hypothenemus hampei) for the purpose of counting a one step for management integrated pest, which is to control initiative with a living organism and the organic time, because in our country have not yet created laws that promote alternatives pleasant environment. In this research the following objectives 1 raised) separating two native strains of Beauveria bassiana in coffee soils present in the Caluma Canton. 2) Determine the activity entomopathogenic species (Beauveria bassiana) on (Hypothenemus hampei). 3) Measure the effect of the fungus on the bit in the laboratory. 4) Know what the ideal of colony forming units of Beauveria bassiana to control the coffee berry borer concentration. The design was completely random (DCA) with a factorial arrangement 2x3x4 with 6 treatments and 4 repetitions: analysis of variance, Tukey 5% effect analysis for the factor was performed to compare the average of treatments, A , correlation analysis and linear regression and analysis of orthogonal polynomials for factor B. the highest average yields were for strain and concentration of treatment; T3: farm Cepa win + 5 * 10 CFU / ml, followed by treatment and concentration; T6: Cepa farm Llaguno + 5 * 10 -10 CFU / ml, which having higher concentration of colony forming units showed better results in all the variables. XVIII